VD_FINDINFO ML / 2019 / 254 vom 31. Dezember 2019 - VD Tribunal cantonal (2019)
DROIT D'ÊTRE ENTENDU, DROIT DE S'EXPLIQUER, RÉPLIQUE, MAINLEVÉE DÉFINITIVE, DÉPENS, AVANCE DE FRAIS, JURIDICTION GRACIEUSE, CESSION LÉGALE | 29 al. 2 Cst., 80 al. 1 LP, 80 LP, 47 LPAv, 1 let. b CPC (CH)